PHYSICAL TEST HERBAL SYRUP OF EMPRIT GINGER (ZINGIBER OFFICINALE VAR. AMARUM) AND LIME (CITRUS AURANTIFOLIA SWINGLE) FOR BODY FITNESS - Riska Chandra Pradana (Poltekkes Kemenkes Surakarta, 2022)
Functional foods can provide health benefits because they contain compounds that are physiologically good for health. The level of public awareness about healthy living through food and drink needs to be increased. This awareness can be obtained through the composition of food and drink that has an attractive taste and color without neglecting certain physiological functions contained in the food or drink so that it is beneficial for the human body. One of the drinks that contain food additives in the form of synthetic dyes is syrup. Many syrups marketed are made of synthetic flavours, artificial sweeteners and synthetic dyes which of course if consumed in the long term can interfere with the health of human organs, so there needs to be innovations in making herbal syrups such as the use of emprit ginger and lime rhizomes. The purpose of this study was to determine the results of the physical test of Emprit ginger rhizome (Zingiber officinale var. amarum) and lime (Citrus aurantifolia swingle) syrup for body fitness. The type of observational research used was to observe and record the results of physical tests on herbal syrups of a combination of Emprit ginger rhizome (Zingiber officinale var. amarum) and lime (Citrus aurantifolia swingle) immune system. The results of the syrup viscosity combination of infunded extracts of Ginger emprit (Zingiber officinale var. Amarum) and lime (Citrus aurantifolia swingle) were 212.0 mPas. The results of this study were the degree of acidity of the syrup with a pH meter of 6.1 organoleptic syrup, dark blue-black in color, the distinctive aroma of ginger and lime, and the sweet, spicy and sour taste and the homogeneity of the syrup, namely homogeneous syrup.